(untitled) (JURNAL ADMINISTRASI PUBLIK, 2022)
This research is motivated by the existence of critical thinking related to the problem of work accidents which are a threat to employers and workers, especially in the North Sulawesi area. The formulation of the research problem is How to Supervise Work Accidents by the Manpower Office of North Sulawesi Province. This study uses the supervisory management theory from Rusdiana and Ghazin (2014). This research is a descriptive research with a qualitative approach. The results of this study indicate that the supervision of the Manpower Office of North Sulawesi Province is still lacking in socializing between the Service and the Company because there are still companies and workers who are not concerned with safety while working so that the number of accidents is still increasing from year to year. This conclusion is the Work Accident Supervision carried out by the North Sulawesi Provincial Manpower Office to overcome work accidents. Suggestions for this research are (1) increasing the number of labor supervisory personnel, (2) supervision related to the visit schedule must be optimized, (3) maximizing the field of labor supervision so that it is carried out properly, (4) Further improving supervision efforts so that more optimal and effective. Keyword:Supervision,Accident,Labor